Use of calcifediol in gilthead seabream (Sparus aurata): Effects on growth performance, biochemical composition, skeletal anomalies and histology - David Dominguez; Pedro Castro; Manon Marmonier; Daniel Arana; Paula Arriagada; Daniel Montero (Aquaculture Reports)
Vitamin D3 is the typical vitamin D supplement in aquafeeds, but this form requires further metabolization to the active form. Calcifediol is used in livestock as an alternative, however it isn’t common in aquaculture. This trial shows the effects of calcifediol in gilthead seabream. 600 seabream (12.8 ± 1.5 g) were fed 5 levels of calcifediol (<2.0, 99.7, 167.4, 298.6 or 825.4 ppb) for 15 weeks. 99.7 ppb of calcifediol improved growth, while 99.7–167.4 ppb reduced the FCR. 99.7 ppb of calcifediol increased the deposition of DHA and omega 3. The level of calcium in the vertebrae increased quadratically up to 99.7 and 167.4 ppb. No effect of the diet was observed on the prevalence of skeletal abnormalities. Mid-intestine fold length increased with 99.7 and 167.4 ppb of calcifediol compared to 825.4 ppb, while mid-intestine lamina propria width was thinner in fish fed 99.7 ppb than those without supplementation. 167.4 ppb calcifediol increased 50 % the percentage of goblet cells per surface area in the anterior intestine compared to those without supplementation. The results indicate that 99.7 ppb improved growth, FCR, whole-body omega3/omega6 ratio and calcium level in the vertebrae, while the highest levels of supplementation reduced growth, vertebrae calcium and mid-intestine fold length, suggesting a toxic effect of high levels of calcifediol in gilthead seabream juveniles.